Foreign Direct Investment and Technology Spillovers: A Review - Elmawazini, Khaled (Université d'Ottawa | University of Ottawa, 2002)
This paper reviews the theory and the empirical studies on the hypothesis that FDI may generate technology spillovers to the host countries. Threre are five sources affecting the scope and significance of the technology spillovers from FDI: (1) linkages b